CLDF dataset of the Enggano word list from 1895 in Stokhof and Almanar's (1987) Holle List - Rajeg, G P W (University of Oxford, 2023)
This is a digitised and processed word list of the 19th-century Enggano (collected in c1895 by Abs vd Noord). The word list appears in Stokhof and Almanar (1987) as part of the collection of word lists in the Indonesian archipelago collected based on the reference word list (the Holle List) (Stokhof 1980). This Holle List contains around more than 1000 lexical items in Dutch and their English and Indonesian translations. The original version of the Enggano word list (Stokhof and Almanar 1987) is not matched with the Dutch, English, and Indonesian translations in the reference Holle List, but appears as a separate publication. However, the Enggano words in the list are provided with Index numbers that originally should be matched "manually" with the Index number of their Dutch, English and Indonesian translations in the reference Holle List. As part of the current project, we have digitised the reference Holle List (https://engganolang.github.io/digitised-holle-list/) as well as this Enggano word list to enable computational and automatic matching between the Enggano forms and their translations in Dutch, English, and Indonesian in the reference Holle List. This dataset also comes with the programmatic R codes to process the raw Enggano word list into a table and then match it with the corresponding translations in the reference Holle List. The Enggano word list in this dataset is conformant to the Cross-Linguistic Data Format (CLDF) specification and we provided the Python code to validate the CLDF specification of the dataset.